CORPORATE SOCIAL RESPONSIBILITY FROM THE PERSPECTIVE OF THE COMPANY PROVIDING EXPRESS COURIER SERVICES : INTERPRETATIVE CASE STUDY (Perner's Contacts, 2020)
The issue of Corporate Social Responsibility (hereinafter CSR) is currently a highly discussed topic. The implementation of CSR in business strategy can contribute to increased competitiveness which is necessary in todays globalized and modern turbulent market environment. CSR application in business means that the company also takes into consideration environmental and social aspects and impacts of its activities, products and services. CSR has influence on how customers see companies. This concept is important not only for customers, but also for other stakeholders such as are the following: investors, employees, the general public, media, the state and other. The Global Reporting Initiative (hereinafter GRI) is an independent international organization that has pioneered sustainability reporting. The GRI Standards are the first global standards for sustainability reporting. They feature a modular, interrelated structure, and represent the global best practice for reporting on a range of economic, environmental and social impacts. The aim of this paper is to recommend an approach to CSR for a company providing express courier services Czech Republic. The attention is primarily focused on those economic, environmental and social aspects of CSR that are considered important by this company with regard to their business sector. The methods of interpretative case study, questionnaire survey and Analytic Network Process (hereinafter ANP) will be used to determine the best CSR strategy for the company providing express courier services in the Czech Republic in accordance with the GRI Standards.
Keywords: Corporate Social Responsibility; Global Reporting Initiative; Analytic Network Process; interpretative case study; globalization; express courier services